Image of the “Patchworky” Germany in the Poetry by P. A. Vyazemski - Sergey S. Zhdanov (Два века русской классики, 2024)
The paper deals with spatial images of Germany in the poems of P. A. Vyazemsky, dating back to the 1840–1870s. There is a marked anthropic element in the poet’s describing German spatial images when the focus of describing is not the landscape itself but its connection with a personality important to the author. Otherwise, the landscape can become a starting point for philosophical reflections on human existence. In addition, Vyazemsky uses both conditional and typed mimesis for the landscape descriptions of Germany. This technique aims to ensure that the reader completes the spatial picture depicted in his imagination by using the ʽreference’ topoi, and weakened spatiality in general. Finally, the article reveals the key variants of the German world-images in the poet’s texts — these are the travesty, romantic, and sentimentalist modes of description. At the same time, the article highlights many literary types that the author uses to characterize the travestied space: German scientist, philistine, and passionate dreamer. The author’s versions of the romantic world-image demonstrate ambivalence in the spatial structure of the chronotope as well as Vyazemsky’s appeal to the Rhine intertext of Russian literature. Various examples of demi-natural idyll represent the sentimentalist world-image.